Defects in autophagy caused by glaucoma-associated mutations in optineurin. (March 2016) - Sirohi, Kapil; Swarup, Ghanshyam
Abstract: Certain mutations in optineurin (gene OPTN ) are associated with primary open angle glaucoma. Optineurin is ubiquitously expressed but it shows high level of expression in certain cells and tissues including retinal ganglion cells. It interacts with many proteins, often acting as an adaptor to link two or more proteins. These interactions play a crucial role in mediating various functions of optineurin such as membrane vesicle trafficking, autophagy, signal transduction etc. Autophagy is basically a quality control mechanism to remove damaged proteins and organelles through lysosomal degradation. Optineurin was identified as an autophagy receptor that directly interacts with autophagosomal protein, LC3, and ubiquitin. These interactions are important for autophagy receptor function. Autophagy receptors recruit their cargo and take it to autophagosomes which fuse with lysosomes to form autolysosomes where degradation of proteins takes place. Optineurin interacts with a motor protein, myosinVI, and this interaction is involved in mediating fusion of autophagosomes with lysosomes. A glaucoma-associated mutant of optineurin, E50K, impairs autophagy as well as vesicle trafficking, leading to death of retinal cells by apoptosis. E50K-OPTN-induced block in autophagy is dependent on a GTPase activating protein, TBC1D17. The E50K mutant also causes other changes in the cells such as altered interaction with TBK1 protein kinase, aggregate formation, generation of reactive oxygen species and inhibition of proteasome, which may contribute to pathogenesis. A polymorphism of optineurin, M98K, associated with glaucoma, causes enhanced autophagy leading to transferrin receptor degradation and apoptotic death of retinal cells. M98K-OPTN-induced autophagic cell death is dependent on Rab12 GTPase. Thus, an optimum level of optineurin-mediated autophagy is crucial for survival of retinal cells, and impaired autophagy is likely to contribute to glaucoma pathogenesis. How impaired autophagy caused by optineurin mutants leads to apoptosis and cell death, is yet to be explored. Highlights: Mutations in OPTN cause glaucoma (E50K, M98K) and ALS. E50K-OPTN impairs autophagy, vesicle traffic and causes aggregate formation. E50K-OPTN-induced block in autophagy is dependent on a GTPase activating protein. M98K-OPTN induces Rab12-dependent autophagy that leads to retinal cell death.